THE CONCEPT OF POLARITY AND CENTRES OF POWER IN INTERNATIONAL RELATIONS - Nuke Faridha Wardhani (Universitas Airlangga, 2021)
This paper explains the concept of polarity and centres of power where the poles are divided into three types in the international system. To be a great power, the states build and maintain their power capability in the system, and that capability is growing in every period, such as the emergence of nuclear power in the Cold War era. Furthermore, the scholars of international relations have different perceptions to determine the poles after the Cold War until this era whether the international system is unipolar or multipolar or even bipolar, as several countries are predicted to be potential great power in the forthcoming years.